Daytime microclimatic impacts of the SOVALP project in summer: A case study in Geneva, Switzerland. (August 2014) - Minella, Flávia Osaku; Krüger, Eduardo; Honjo, Susan; Goyette, Stéphane; Hedjazi, Alexandre
The Société Simple de Valorisation de Terrains à Genève-La Praille (SOVALP) project was conceived as a means of providing adequate housing within redevelopment policies during the last decades in Geneva, Switzerland including, among other measures, ideas for recovering an old industrial site. The SOVALP project is aimed at the construction of a mixed-use urban center around a multimodal hub with a built area around 300, 000 m 2 . The present study analyzes the daytime impacts on outdoor thermal comfort from such an intervention in the urban environment, based on microclimatic field measurements and computer simulations. The microclimatic variables were collected simultaneously at two monitoring points during daytime in August 2011, around the Praille Railway Station. From calculations of the outdoor comfort indices Physiological Equivalent Temperature Index (PET) and Universal Thermal Climate Index (UTCI) derived from field measurements, it was found that the current situation in summer presents a high level of heat stress. By means of the ENVI-met software microclimate simulations, beneficial effects from the SOVALP project arose, pointing to reductions in air temperature as high as 2.2°C within the redeveloped area and of 1.2°C in the entire area evaluated. Changes in PET and UTCI point to a reduction in heat stress categories.